2021
DOI: 10.1177/0956797620975774
|View full text |Cite
|
Sign up to set email alerts
|

Using Body Ownership to Modulate the Motor System in Stroke Patients

Abstract: Recent findings suggest that body ownership can activate the motor system in the absence of movement execution. Here, we investigated whether such a process promotes motor recovery in stroke patients. A group of patients with left-hemisphere damage ( N = 12) and chronic motor deficits completed an immersive virtual reality training (three sessions of 15 min each week for 11 weeks). Patients sat still and either experienced (first-person perspective) or did not experience (third-person perspective) illusory own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 56 publications
(76 reference statements)
1
21
0
Order By: Relevance
“…A study by Seinfeld and colleagues 24 found that participants who performed the motor task through a Leap motion sensor, seeing one’s virtual hand, felt a stronger sense of body-ownership and the sense of agency and showed better task performance than those who performed the task with a keyboard and could not see one’s avatar. In relation to clinical population, Tambone and colleagues 25 demonstrated that observing the virtual body’s movements from a first-person perspective helps increase body-ownership, which subsequently promotes stroke patients' motor recovery by accessing their motor functioning. These studies seem to support a positive functional link between virtual embodiment and improved motor abilities and performance.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Seinfeld and colleagues 24 found that participants who performed the motor task through a Leap motion sensor, seeing one’s virtual hand, felt a stronger sense of body-ownership and the sense of agency and showed better task performance than those who performed the task with a keyboard and could not see one’s avatar. In relation to clinical population, Tambone and colleagues 25 demonstrated that observing the virtual body’s movements from a first-person perspective helps increase body-ownership, which subsequently promotes stroke patients' motor recovery by accessing their motor functioning. These studies seem to support a positive functional link between virtual embodiment and improved motor abilities and performance.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable body of research suggests that the full body illusion induces also distinct behavioral, cognitive, and emotional changes. Several studies focused on the motor domain and examined how feeling ownership of a moving avatar triggers a correspondent self-attribution of the avatar's movements and/or their properties [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Other studies have investigated interpersonal relationships and the way in which illusory ownership modulates harassment, motherhood, and counseling behavior [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that use of interventions, such as visual illusion and imagery, targeting the individuals’ body ownership and improve representation of the upper limb may be beneficial if applied prior to conventional motor rehabilitation training in stroke [ 84 ]. What is more, a strong feeling of body ownership may well contribute to successful restoration of motor function [ 85 ]. That body perception disturbance is more common in those who experience pain post-stroke may indicate that such a relationship could be particularly relevant for stroke survivors with chronic pain.…”
Section: Discussionmentioning
confidence: 99%